2020
DOI: 10.1080/0305764x.2020.1724261
|View full text |Cite
|
Sign up to set email alerts
|

Modern foreign languages: decision-making, motivation and 14–19 schools

Abstract: This article reports on an exploratory study comparing motivation and student choice in modern foreign language lessons in secondary schools (11-16 or 11-18) and schools for 14-19 year olds in England. The study uses data gathered from 634 Year 10 students (aged 14-15), and uses selfdetermination theory to compare motivation amongst students in the two types of schools. It finds that student motivation differed significantly in each, with students in 14-19 schools displaying more autonomous motivation. Studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Though SDT has been eclipsed, numerically, by other theories in the intervening years (Boo et al, 2015), its impact has remained strong-perhaps due to its theoretical and empirical consistency. That is, SDT research in the interim has indicated its robust applicability in multiple language learning contexts, including elementary school (Carreira, 2012), secondary school (Fryer & Oga-Baldwin, 2019), university (Joe et al, 2017), online learning (K. C. Chen & Jang, 2010), and independent language learning (Mynard & Shelton-Strong, 2022), with studies representing each of these contexts in multiple cultural settings, including China (C. Chen et al, 2021), Iran (Karbakhsh & Safa, 2020), Malaysia (Khong & Kabilan, 2020) and Saudi Arabia (Alamer & Lee, 2021), in addition to the more commonly represented samples found in the United States (Davis, 2020), the UK (Parrish, 2020), Belgium (Rogiers et al, 2020), and Canada (Noels et al, 2019).…”
Section: Self-determination Mini-theories In Second Language Learning...mentioning
confidence: 99%
“…Though SDT has been eclipsed, numerically, by other theories in the intervening years (Boo et al, 2015), its impact has remained strong-perhaps due to its theoretical and empirical consistency. That is, SDT research in the interim has indicated its robust applicability in multiple language learning contexts, including elementary school (Carreira, 2012), secondary school (Fryer & Oga-Baldwin, 2019), university (Joe et al, 2017), online learning (K. C. Chen & Jang, 2010), and independent language learning (Mynard & Shelton-Strong, 2022), with studies representing each of these contexts in multiple cultural settings, including China (C. Chen et al, 2021), Iran (Karbakhsh & Safa, 2020), Malaysia (Khong & Kabilan, 2020) and Saudi Arabia (Alamer & Lee, 2021), in addition to the more commonly represented samples found in the United States (Davis, 2020), the UK (Parrish, 2020), Belgium (Rogiers et al, 2020), and Canada (Noels et al, 2019).…”
Section: Self-determination Mini-theories In Second Language Learning...mentioning
confidence: 99%
“…Results from citation analysis have demonstrated that in the past two decades, SDT has become one of the most established motivational theories in L2 learning and has been robustly applied in multiple cultural settings. For instance, Chen et al (2021) have applied the basic psychological needs theory and the relationship motivation theory in the Chinese context, Alamer and Lee (2021) in the Saudi Aribian context, Carreira (2012) in the Japanese context, and more commonly in the American ( Davis, 2022 ) and British contexts ( Parrish, 2020 ). Moreover, several mini-theories (e.g., organismic integration theory, cognitive evaluation theory, basic psychological needs theory, and goal contents theory) of SDT have also been generated ( Al-Hoorie et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there are two kinds of motivation: intrinsic motivation (IM) and extrinsic motivation (EM) [ 8 ]. The actions that an individual performs to satisfy his own needs are considered intrinsic motivation [ 9 ], i.e., why a person performs certain actions due to his own interests [ 10 ]. On the other hand, extrinsic motivation moves an individual to carry out actions in order to satisfy his environment [ 11 ].…”
Section: Introductionmentioning
confidence: 99%